If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7 + x) = -36 (7 * 2 + x * 2) = -36 (14 + 2x) = -36 Solving 14 + 2x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 2x = -36 + -14 Combine like terms: 14 + -14 = 0 0 + 2x = -36 + -14 2x = -36 + -14 Combine like terms: -36 + -14 = -50 2x = -50 Divide each side by '2'. x = -25 Simplifying x = -25
| b/5+1/3=17 | | 11x=16500 | | (7+x)=-36 | | 5(v-7)=-45 | | y-13=-.8x-(-5) | | 0.6666x+1=x-4 | | -6t+t^2=0 | | V=Vlw | | 4r=250 | | y+8=-4 | | 50x^2+25x=0 | | y+(-12)=24 | | 8/7+7m/5=96/35 | | 5d+9+2+3d= | | 1=5n-5-7n | | 3=3v+6 | | 90-k=12 | | 20x+5y=180 | | y=17x^2+14x-9 | | -11t=11 | | -27+9x=12x+21 | | 2.8+3.2a=2.3a-(-9a+0.2) | | x-78=4x-24 | | 4.603y-1.842=-4.2 | | 2x+12=3x+x | | 6-4(8z+2)=-(-3z+1)+1 | | 3x^2+60x-225=0 | | 5x^2+10x=185 | | -4=5-3u | | 12-n=20 | | (3)+9(-6)-1= | | -12m=-96 |